The Effect of Astaxanthin on Ochratoxin A-Induced Intestinal Injury in Chickens Through RIPK1/RIPK3/MLKL Pathway - Fan, Ruiwen; Tian, Wenqi; Jin, Bo; Sun, Yuhang; Long, Miao; Yang, Shuhua; Li, Peng (Antioxidants, 2025)
Ochratoxin A (OTA), as a mycotoxin, can contaminate a variety of feeds and foods. Existing studies have shown that the main toxicity of OTA to organisms is nephrotoxicity, but the toxic mechanism to other organs is still worthy of further study. Whether OTA causes intestinal damage through the necroptosis pathway mediated by RIPK1/RIPK3/MLKL remains to be elucidated. Astaxanthin (AST), a feed additive with strong antioxidant properties, was used as an antidote to evaluate the alleviation effect on OTA-induced intestinal injury and the underlying mechanism in this research. Chickens are the most sensitive animals to OTA except pigs. Therefore, 70 white-feathered chickens (n = 15) and Chicken Small Intestinal Epithelial Cells (CSIECs) were used as experimental subjects. Experimental models were established by single or combined exposure of OTA (1.0 mg/kg on chickens for 21 d; 2 μM on CSIEC for 24 h) and AST (100 mg/kg on chickens for 21 d; 40 μM on CSIEC for 24 h). In this study, AST significantly ameliorated OTA-induced intestinal damage by restoring the expression of tight junction proteins (Occludin-1, Claudin-1, and ZO-1), attenuating severe histopathological alterations, mitigating the inflammatory response (elevated pro-inflammatory cytokines and reduced anti-inflammatory mediators), and suppressing necroptosis through downregulation of RIPK1, RIPK3 and MLKL expression. Combined evidence from animal experiments and cell culture experiments demonstrated that AST alleviated the necroptosis and inflammation caused by OTA in CSIECs and the intestine of chickens through the RIPK1/RIPK3/MLKL signaling pathway, thereby reducing the damage caused by OTA.